Variations in Properties of Soils Brought about by Termite Activity on Plants - Singh, S. B.; Gangopadhyay, S. K.; Banerjee, S. K. (Indian Forester, 1987)
Properties of termite (Odontotormes obesus) galleries developed on the stem of different living plants and termite mounds of the area Were compared. The study revealed that galleries. Contained greater concentration of calcium, magnesium and potassium than the mounds suggesting that the activities of termite, during gallery formation enhanced the nutrient status of the medium. The present study shows that the enhanced nutrients were derived from the bark of the plants used by termite as food and concentrations of the nutrients in the galleries depended both on the concentration of nutrients in the bark and on the amount of bark used as termite food.